The Impact Of Psychological Well-Being And Work Environment Toward Work Engagement Of Millennial Employee In Jakarta - Harimurti, Muhammad Kevindra Putra; Wulansari, Puspita (eProceedings of Management, 2024)
As the Millennial generation approaches its peak productive years, it becomes pivotal in fostering the nation'seconomic advancement. Despite extensive discussions surrounding Millennials, most dialogues are predicated onsubjective narratives devoid of empirical substantiation, potentially resulting in detrimental outcomes. It is necessaryto enhance millennial employees' psychological well-being and engagement by ensuring a supportive workenvironment. Consequently, organizations must cultivate an atmosphere that enhances Psychological Well-Being.Various strategies can be employed to achieve this, including providing psychological support for staff, establishingan encouraging and positive Work Environment, and encouraging a balanced work-life dynamic. This study employsConfirmatory Factor Analysis (C.F.A.) to validate or verify the proposed theoretical model. The proposed analyticalframework incorporates multiple latent variables assessed through various indicator variables. Structural EquationModeling (S.E.M.) serves as the methodological instrument for data collection. The demographic focus of this studyencompasses millennial employees from Jakarta, totalling 2,828,858 individuals. An error margin of 10% dictated theselection of 250 participants for the study sample. Findings from the analysis indicate that the variables ofPsychological Well-Being, Work Environment, and Work Engagement are classified within the 'excellent' range. Ithas been observed that the variable of Psychological Well-Being exerts influence over the Work Engagement ofMillennial Employees in Jakarta. Similarly, the Work Environment is noted to impact the Work Engagement of theseemployees. Keywords-psychological well-being, work environment, work engagement, millennial employee